Development of an Augmented Reality-Based Educational Media for East Kalimantan Endemic Plants - Satria, Bagus; Ramadhani, Fajar; Imron, Imron (STMIK Widya Cipta Dharma, 2025)
East Kalimantan is a region with a high level of biodiversity, including endemic plant species such as Eusideroxylon zwageri (Ulin), Coelogyne pandurata (Black Orchid), and Nepenthes spp. (Pitcher Plant). Unfortunately, public awareness especially among young generations of the importance of conserving these local flora remains low due to the lack of engaging and contextual learning media. This study aims to develop an Augmented Reality (AR)-based educational media that visualizes interactive 3D models and descriptive information about East Kalimantan endemic plants. The research applies an interactive multimedia-based Research and Development (R&D) approach through stages of observation, documentation, 3D modeling, application development using Unity and Vuforia SDK, and testing involving students from local schools. Evaluation was conducted using pre-test and post-test designs, along with expert validation on content and usability. The results show that the developed AR application effectively enhances students’ understanding of local biodiversity and environmental awareness. This media also provides an innovative solution for digital conservation education that integrates technology with local ecological content.